Neonatal small left colon syndrome - Radiological diagnosis by gastrografin contrast study - Sharma, Shashi; Sharma, B B; Chamaria, Komal; Bansal, Kush (Indian Journal of Child Health, 2015)
Neonatal small left colon syndrome (NSLCS) is one of the suspected diagnoses if the neonate does not pass meconium within 24 h of birth. Radiological contrast studies play a vital role in diagnosing and treating the entity. We report a case where the newborn did not pass meconium till 4 days of birth and which on gastrografin studies was diagnosed as a case of NSLCS.